2020
DOI: 10.1681/asn.2020060827
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Asymptomatic COVID-19 Infection in Hemodialysis Patients Detected Using Serologic Screening

Abstract: BackgroundStrategies to minimize the risk of transmission and acquisition of COVID-19 infection in patients with ESKD receiving in-center hemodialysis have been rapidly implemented across the globe. Despite these interventions, confirmed COVID-19 infection rates have been high in the United Kingdom. Prevalence of asymptomatic disease in an adult hemodialysis population has not been reported. Also, to our knowledge, the development of humoral response to SARS-CoV-2 has not been previously reported in this popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
5
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(159 citation statements)
references
References 15 publications
(14 reference statements)
5
145
5
4
Order By: Relevance
“…Nonetheless, the seroprevalence within this group may be markedly different from that of the general population. For example, a study of U.K. dialysis patients found seroprevalence of about 36%, several times higher than that obtained using a very large random sample of the English population [21,22]. Similarly, a recent U.S. study found a seropositive rate of 34% for dialysis patients in New York state that was more than twice as high as the seroprevalence in a random sample of New York residents [10,23 Our critical review has also underscored the pitfalls of seroprevalence studies based on "convenience samples" of residual sera collected for other purposes.…”
Section: Sampling Framementioning
confidence: 75%
“…Nonetheless, the seroprevalence within this group may be markedly different from that of the general population. For example, a study of U.K. dialysis patients found seroprevalence of about 36%, several times higher than that obtained using a very large random sample of the English population [21,22]. Similarly, a recent U.S. study found a seropositive rate of 34% for dialysis patients in New York state that was more than twice as high as the seroprevalence in a random sample of New York residents [10,23 Our critical review has also underscored the pitfalls of seroprevalence studies based on "convenience samples" of residual sera collected for other purposes.…”
Section: Sampling Framementioning
confidence: 75%
“…In a multicenter retrospective study in Wuhan, China, 47% of SARS-CoV-2-infected people, who were mostly asymptomatic, were diagnosed with serological tests after negative RT-PCR ( Tang et al, 2020 ), as demonstrated by Clarke and colleagues. A high seroprevalence of SARS-CoV-2 antibodies was noted in asymptomatic or PCR-negative patients receiving in-center hemodialysis, suggesting that current diagnostic screening strategies may be limited in their ability to detect acute infection ( Clarke et al, 2020 ). In our study, we found a high seroprevalence of SARS-CoV-2 with the Abbott test, but low sensitivity in identifying virus carriers and low positive predictive values in 2407 serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…21 Interestingly, a study addressing the seroprevalence of SARS-CoV-2 antibodies in a hemodialysis population in the United Kingdom found that around 36.2% of the patients tested positive for COVID-19 and almost half were asymptomatic. 32 …”
Section: Discussionmentioning
confidence: 99%